Experimental and numerical investigation of ground heat exchangers in the building foundation - Kayaci, Nurullah; Demir, Hakan; Kanbur, Baris Burak; Atayilmaz, Sevket Ozgur; Agra, Ozden; Acet, Rusen Can; Gemici, Zafer (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
The current study proposes a novel method with the experimental and numerical studies for the ground source heat pumps, which are known as environment-friendly and efficient heating & cooling systems to overcome their economic drawbacks in the applied engineering operations. The experimental studies are carried out in the newly built Central Laboratory of Yildiz Technical University, Davutpasa Campus, Istanbul, Turkey. The long parallel heat exchanger pipes are placed in two different layers of the ground that are (1) under the building foundation (ground layer), and (2) in the building foundation (concrete layer), respectively. Besides, a unique numerical model is developed in MATLAB environment to obtain temperature distributions in ground and concrete layers. Then, the numerical outputs are validated with the observed experimental results. The daily average of the energy amount extracted from the Ground and Concrete Loops was found as 5.51 and 4.63 kWh/day, respectively. The results are found satisfying for real applications in the building foundations.
Keywords: Ground source heat pump; Computational modeling; Horizontal heat exchanger; Transient analysis; Building energy simulations; PUMP SYSTEM; THERMAL PERFORMANCE; ENERGY-PILES; SIMULATION; EFFICIENCY; DESIGN; MODELS; Thermodynamics; Energy & Fuels; Mechanics